2016
DOI: 10.3389/fnins.2016.00572
|View full text |Cite
|
Sign up to set email alerts
|

Motor Dysfunctions and Neuropathology in Mouse Models of Spinocerebellar Ataxia Type 2: A Comprehensive Review

Abstract: Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant ataxia caused by an expansion of CAG repeats in the exon 1 of the gene ATXN2, conferring a gain of toxic function that triggers the appearance of the disease phenotype. SCA2 is characterized by several symptoms including progressive gait ataxia and dysarthria, slow saccadic eye movements, sleep disturbances, cognitive impairments, and psychological dysfunctions such as insomnia and depression, among others. The available treatments rely on palliativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 124 publications
0
17
0
Order By: Relevance
“…Patients suffer from ataxia, parkinsonism, dysarthria, dysmetria, action tremor, hypotonia, and slow saccades (Buijsen et al, 2019). Several structures like brainstem, spinal cord, thalamus, cranial nerves, and muscles are affected (Rub et al, 2003;Lastres-Becker et al, 2008b), but the progressive atrophy of the cerebellum with Purkinje cell death is the primarily sign of neurodegeneration (Estrada et al, 1999;Hansen et al, 2013;Alves-Cruzeiro et al, 2016).…”
Section: Sca2mentioning
confidence: 99%
“…Patients suffer from ataxia, parkinsonism, dysarthria, dysmetria, action tremor, hypotonia, and slow saccades (Buijsen et al, 2019). Several structures like brainstem, spinal cord, thalamus, cranial nerves, and muscles are affected (Rub et al, 2003;Lastres-Becker et al, 2008b), but the progressive atrophy of the cerebellum with Purkinje cell death is the primarily sign of neurodegeneration (Estrada et al, 1999;Hansen et al, 2013;Alves-Cruzeiro et al, 2016).…”
Section: Sca2mentioning
confidence: 99%
“…Pathophysiological mechanisms underlying the gain of toxic functions of mutated ataxin-2 include toxic accumulation of cytoplasmatic protein aggregates, abnormal neuronal calcium signaling, abnormal protein recycling, proteolytic cleavage, transcriptional and translational dysregulation, and mitochondrial dysfunction ( 1 , 109 , 110 ). Recently, a mechanism of RNA toxicity was suggested for SCA2.…”
Section: Genotypical Featuresmentioning
confidence: 99%
“…Previous resting state functional MRI studies also observed the associations between the lingual gyrus and psychiatric symptoms such as depression, loneliness, and anxiety (Lan et al., 2015; Liu et al., 2015, 2017). Although psychiatric symptoms were not reported in the five included studies, they are common in SCA2 patients (Alves‐Cruzeiro, Mendonca, Pereira, Almeida, & Nobrega, 2016; Fancellu et al., 2013; Schmitz‐Hübsch et al., 2011). Therefore, the lingual gyrus may also play a role in emotional processing.…”
Section: Discussionmentioning
confidence: 99%